2015
DOI: 10.1016/j.mattod.2014.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal self-assembly concepts for light management in photovoltaics

Abstract: Colloidal particles show interaction with electromagnetic radiation at optical frequencies. At the same time clever colloid design and functionalization concepts allow for versatile particle assembly providing monolayers of macroscopic dimensions. This has led to a significant interest in assembled colloidal structures for light harvesting in photovoltaic devices. In particular thin-film solar cells suffer from weak absorption of incoming photons. Consequently light management using assembled colloidal structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 188 publications
(224 reference statements)
0
126
0
3
Order By: Relevance
“…[139] In one notable exception, Park et al recently reported the use of Au NP NPCs for the enhancement of organic photovoltaic devices. [140] Their results are interesting, since incorporation of nanoparticles directly into the active layer of a bulk-heterojunction solar cell is difficult due to 3D phase separation between the donor and acceptor phases, a delicate process for which the presence of particles or clusters is usually detrimental.…”
Section: Progress Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…[139] In one notable exception, Park et al recently reported the use of Au NP NPCs for the enhancement of organic photovoltaic devices. [140] Their results are interesting, since incorporation of nanoparticles directly into the active layer of a bulk-heterojunction solar cell is difficult due to 3D phase separation between the donor and acceptor phases, a delicate process for which the presence of particles or clusters is usually detrimental.…”
Section: Progress Reportmentioning
confidence: 99%
“…[140] Their results are interesting, since incorporation of nanoparticles directly into the active layer of a bulk-heterojunction solar cell is difficult due to 3D phase separation between the donor and acceptor phases, a delicate process for which the presence of particles or clusters is usually detrimental. [139] The NPCs used were prepared in situ at the hole-blocking layer (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) from silver nanoprisms by galvanic replacement with Au + , resulting in close-packed Au NPCs with considerable field enhancement. With such a structure, the photoconversion efficiency could be improved by a relative 14%.…”
Section: Progress Reportmentioning
confidence: 99%
“…bottom-up) to fabricate Mie scatterers for solar cells need to be explored. Although wet chemical techniques are used to fabricate Mie scattering structures (Araújo A. et al, 2017;Karg M. et al, 2015), more industrially compatible techniques are desirable. A recent work by (Giannakoudakis and Di Vece, 2017) shows that TiO 2 Mie scatterers can be produced with a gas aggregation cluster source and combined with a-Si thin films.…”
Section: Mie Scatterersmentioning
confidence: 99%
“…bottom up) to fabricate Mie scatterers for solar cells need to be explored. Although wet chemical techniques are used to fabricate Mie scattering structures [14,15], more industrial compatible techniques are desirable.…”
Section: Introductionmentioning
confidence: 99%